2015
DOI: 10.3390/ijerph120100652
|View full text |Cite
|
Sign up to set email alerts
|

Work Related Stress, Burnout, Job Satisfaction and General Health of Nurses

Abstract: Gaps in research focusing on work related stress, burnout, job satisfaction and general health of nurses is evident within developing contexts like South Africa. This study identified the relationship between work related stress, burnout, job satisfaction and general health of nurses. A total of 1200 nurses from four hospitals were invited to participate in this cross-sectional study (75% response rate). Participants completed five questionnaires and multiple linear regression analysis was used to determine si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

42
409
1
48

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 580 publications
(547 citation statements)
references
References 51 publications
42
409
1
48
Order By: Relevance
“…As for marital status, there is a higher prevalence of depression in people who do not have close interpersonal relationships, without children, or who are separated or divorced (13) . Studies carried out with nursing staff working in an intensive care unit showed that the prevalence of depressive symptoms is higher in professionals working in the night shift and that there was a significant association between depressive symptoms and work shift (13,(22)(23)(24) , a contradictory result to this (1) : using Pearson's correlation test. Burnout and depressive symptoms in intensive care nurses: relationship analysis Vasconcelos EM, Martino MMF, França SPS research.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…As for marital status, there is a higher prevalence of depression in people who do not have close interpersonal relationships, without children, or who are separated or divorced (13) . Studies carried out with nursing staff working in an intensive care unit showed that the prevalence of depressive symptoms is higher in professionals working in the night shift and that there was a significant association between depressive symptoms and work shift (13,(22)(23)(24) , a contradictory result to this (1) : using Pearson's correlation test. Burnout and depressive symptoms in intensive care nurses: relationship analysis Vasconcelos EM, Martino MMF, França SPS research.…”
Section: Discussionmentioning
confidence: 97%
“…Due to the exhaustive and stressful work, these professionals are more likely to develop occupational stress, which is an important determinant of depression and burnout (1) . When work-related stress transcends adaptive levels without an effective coping mechanism, it is called burnout or burnout syndrome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Due to exhaustive and tense work, these professionals are more likely to develop occupational stress, which is an important determinant of depression and of other psychic diseases. 2 Depression is defined as a state of psychic suffering, which has consequences on interpersonal relationships.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, studies have mostly focused on the effects of work stress in the nursing environment (Khamisa, Oldenburg, Peltzer, & Ilic, 2015;Khamisa, Peltzer, & Oldenburg, 2013;Kumari & De Alwis, 2015;Makola, Mashegoane, & Debusho, 2015;Sekol & Kim, 2014), with the effect of personal stress in nursing being less explored. Evidence shows that work stress contributes to higher burnout levels among nurses and is associated with lower job satisfaction (Graham, Davies, Woodend, Simpson, & Mantha, 2011).…”
Section: Introductionmentioning
confidence: 99%